Modern problems of linguistics and methods of teaching English - Norjon Gafurova (International Consortium of Education and Culture Research Studies, 2019)
This article discusses the problem of intercultural communication, in which background knowledge plays an important role. Referring to our research, we see a solution to this problem in expanding the students' background knowledge, i.e. familiarization of students with the realities, traditions and customs of English-speaking countries. Accordingly, several components help to better master the language being studied, as a result of which a system of knowledge of a foreign language is formed, implemented and operates as a means of communication.